Social disorganization and crime (Archives of Criminology, 1988)
The notion of social disorganization, rather seldom used in sociology today, used to have a broad application in the American sociology of the 1920-1940s, in particular in the analysis of effects of such social processes as mass migrations, urbanization and industralization. The term of social disorganization was given to the negative effects of social changes related to these processes. Presently, this term is sometimes used in the analysis of the contemporary highly developed societes when discussing the stability of their cultural systems and the functioning of their basic social institutions.            There are also in sociology many definitions of social disorganization; generally, it may be defined as the state of a disturbed social balance resulting from a social change first and foremost. What is the value of this term for a criminologist? Irrespective of the type of definition of social disorganization applied, one of its basic determinants is considered to be crime both as a mass phenomenon and as an individual act. Therefore this term is used in sociology since a long time to designate social phenomena that are rather varied for that matter.            Traditionally, the term "social disorganization’’ meant in criminology social situation f und in the so-called delinquency areas which emerged in the period of vehement development of American cities as a result of mass migrations in search of livelihood. In traditional handbooks of criminology, a generalization of experimental findings concerning the processes that take place in delinquency areas is usually called the theory of social disorganization.            Not long ago, a work by R. Kornhauser was published which is an attempt at a new approach to the development of the sociological theory of crime. In the work, two basic analytic models of investigation of crime conditions are distinguished. One of them is the model of social disorganization interpreted as a relative lack of a formulated system of values in a given  culture and as a disturbed relationship between culture and the social structure. Two theoretical approaches can be distinguished here which are derived from the notion of social disorganization. They are: the model of social control and the model of strain. According to the first of them, disorganization results in the weakening of social control which manifests itself in disturbances either of the process of socialization or of the functioning of the basic social institutions, being thus conductive to the emergence of a delinquent or otherwise deviant behaviour. Acording to the second of the above-mantioned approaches, social disorganization brings about the rise of pressure towards delinquent behaviour, the strain resulting from the divergence between the socially formed aspirations and the expectations as to their realization. According to the authors of this classification, the main representatives of the social control trend are Thrasher as well as Shaw and McKay, and of the strain one-Merton, Cohen who derived his theoretical discussion from Merton's conception of anomy, and Cloward and Ohlin. The notion of social disorganization is also referred to in works of other theoreticians of criminology, such as for instance Sutherland and Sellin. They both refer to the results of the societies's cultural differentiation, that of the structure of norms in particular. Cultural diffrentiation, which is one of the effects of social disorganization, may sometimes - in extreme cases – assume the form of a conflict of cultures, i.e. of a state of fundamental conflict between the systems of norms and values of the separate social groups.            Social disorganization cannot be treated as an explicitly defined and measurable social phenomenon. Instead, we can measure some situational determinants of disorganization which can be applied in studies of such social processes as migrations, vehement urbanization, rapid industrial development of regions with no industrial traditions, socio-economic crises, etc., on the one hand, and in studies of a disturbed functioning of social institutions that are particularly important for the society (the family in particular) on the other hand.In Poland, there is quite a rich tradition of investigating some aspects of social disorganization, as for instance studies of the effect urbanization and industrialization have on crime, of the symptoms of disorganization in urban environment, and above all of various aspects of family disorganization and their connection with delinquency.            The notion of social disorganization, though susceptible of various interpretations, nevertheless seems useful in criminology as it makes it possible to combine into a syndrome the various traits of certain social situations that are conductive to delinquent behaviour.